Synthesis, Characterization and Antimicrobial Evaluation of Some Arylidenehydrazonofuropyrimidines and Thienopyrimidines: Synthesis and Characterization of Pyrimidines (Biological Sciences - PJSIR, 2009)
Cyclization of heteroaromatic o-aminoester with formamide afforded furo[2,3-d]pyrimidin-4(3H)-one which was then chlorinated with thionyl chloride followed by displacement by hydrazine hydrate to furnish hydrazinofuro [2,3-d]pyrimidine. Reaction of hydrazino derivative with formic acid gave furo[3,2-e][1,2,4]triazolo[4,3-c]pyrimidine. Treatment of hydrazino derivative with aromatic aldehydes afforded arylidenehydrazonofuro[2,3-d]pyrimidine deriva- tives. Reaction of o-aminonitrile with carbon disulphide, followed by methylation with methyl iodide and subsequent reaction with hydrazine hydrate afforded hydrazinothieno[2,3-d]pyrimidine. 14 derivatives were synthesized. Some of these derivatives exhibited pronounced antimicrobial activities against S. typhi, S. aureus, S. dysenteriae, V. cholerae, C. lunata, A. alternata, C. corchori, F. equeseti and M. phaseolina.